2005
DOI: 10.1039/b501370d
|View full text |Cite
|
Sign up to set email alerts
|

Competing elimination and substitution reactions of simple acyclic disulfides

Abstract: MP2/aug-cc-pVDZ and B3LYP/cc-pVDZ calculations of the reactions of CH3SSR (R = H or CH3) with fluoride, hydroxide or allyl anion in the gas-phase were performed to determine the mechanism for both elimination and substitution reactions. The elimination reactions were shown to follow the E2 mechanism. The substitution reactions with hydroxide and fluoride proceed by the addition-elimination mechanism, but those with allyl anion proceed by the SN2 mechanism. The elimination reactions with F- and HO- are preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
0
19
1
Order By: Relevance
“…14 It was suggested on the basis of CCSD and DFT calculations that the transition state for RS-attack on RS-SR proceeds in most cases by a trianionic [ δ− S-S-S δ− ] structure, although the energy of the corresponding minimum attending an addition-elimination mechanism was very close in energy. 15 To date, we have found no systematic theoretical study of the attack of phosphorus on the disulfide linkage. In a recent theoretical study 16 we reexamined the nature of the intermediatetransition structure for the S N 2 attack of CH 3 S − on dimethyl disulfide at several levels of theory including CCSD 17 and determined the effect of solvation on this thiol-disulfide interchange using the COSMO 17d solvent model in addition to the inclusion of explicit waters of solvation.…”
Section: Introductionmentioning
confidence: 99%
“…14 It was suggested on the basis of CCSD and DFT calculations that the transition state for RS-attack on RS-SR proceeds in most cases by a trianionic [ δ− S-S-S δ− ] structure, although the energy of the corresponding minimum attending an addition-elimination mechanism was very close in energy. 15 To date, we have found no systematic theoretical study of the attack of phosphorus on the disulfide linkage. In a recent theoretical study 16 we reexamined the nature of the intermediatetransition structure for the S N 2 attack of CH 3 S − on dimethyl disulfide at several levels of theory including CCSD 17 and determined the effect of solvation on this thiol-disulfide interchange using the COSMO 17d solvent model in addition to the inclusion of explicit waters of solvation.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum recorded during its reaction with dimethyl disulfide shows that besides the expected thiophilic reaction (the presence of m/z 47 CH 3 S - ion), also the formation of m/z 93 ion is observed. According to the proposal of Grabowski and Zhang [1], supported later by the calculations performed by Bachrach et al [6], this ion should possess the hemithioacetal structure CH 3 S-CH 2 -S - . Our calculations (Figure 4) fully confirmed this structure.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, Bachrach and Pereverzev conducted theoretical calculations for gas-phase reaction of methyl disulfide and dimethyl disulfide with F - , OH - and allyl anion [6]. The goal of these studies was to determine the mechanism of the occurring elimination and substitution reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[10,12,24] However, a common characteristic of these bridges is that they cleave easily in reduction processes. [31][32][33][34][35][36][37] In all cases, it was found that the SAS or the SeASe bond fission is the dominant process, although in the systems investigated the substituents attached to S or Se were either identical or ones of similar electronegativity. [25][26][27][28] Consequently, the most powerful techniques in protein sequencing are based on the cleavage of SAS or SeASe bridges within the protein, but the mechanisms at the molecular level are far from being well understood.…”
Section: Introductionmentioning
confidence: 92%
“…[29] Several studies have been published in an effort to characterize these bonds [30] and the intrinsic mechanisms of SAS and SeASe bond cleavage in electron attachment processes [27,28] or in nucleophilic attacks. [31][32][33][34][35][36][37] In all cases, it was found that the SAS or the SeASe bond fission is the dominant process, although in the systems investigated the substituents attached to S or Se were either identical or ones of similar electronegativity. It has been shown that when the substituents attached to the chalcogen atoms are very electronegative, cleavage of disulfide or diselenide bonds does not take place in electron attachment processes and the fission of the bond between the chalcogen and the substituent becomes the more favorable process.…”
Section: Introductionmentioning
confidence: 99%